1990
DOI: 10.2466/pms.1990.71.1.281
|View full text |Cite
|
Sign up to set email alerts
|

Body-Image and Body-Beautification among Female College Students

Abstract: Women's body-image has social and personal implications. Judgments about the body can be based on appearance (public body-consciousness), internal sensations (private body-consciousness) or body-effectiveness (body-competence). The correlates of body-image and beautification were studied in a group of 245 female undergraduates who completed a body-beautification questionnaire, the Body-consciousness Inventory, the Body-cathexis/Self-cathexis Scale, and questions on feminist identification. Significant correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Past research examining the role of feminism in relation to clinical outcomes has generally used measures of feminist beliefs, rather than feminist identity (for an exception, see Kelson et al 1990). In the current study, we measured feminist identity as opposed to beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research examining the role of feminism in relation to clinical outcomes has generally used measures of feminist beliefs, rather than feminist identity (for an exception, see Kelson et al 1990). In the current study, we measured feminist identity as opposed to beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that women who self-identified as feminist judge their bodies based on whether they feel healthy and suggested that nonfeminists may judge their bodies based on its appearance (Kelson et al 1990). A recent study indicated that an intervention focusing on feminist theories of body image worked both to increase feminist self-identification (as assessed by a Likert-type scale) and decrease negative body image (Peterson et al 2006).…”
Section: Feminism and Body Concernsmentioning
confidence: 97%
“…Ojerholm and Rothblum (1999) found that neither feminist self-identification (measured on a Likert-type scale) nor attitudes toward feminism were related to body image among undergraduate college women, although feminist identity and positive attitudes toward feminism were related to less negative attitudes toward fat people in general. Only two studies have asked women to directly state whether they self-identify as a feminist, whereas the others have measured feminist attitudes or the degree to which women consider themselves feminists (Garner, 1997;Kelson et al, 1990). This is an important distinction, as many women endorse feminist attitudes, but fewer actually identify themselves as a "feminist" (Williams & Wittig, 1997).…”
Section: Feminism and Beauty Idealsmentioning
confidence: 99%
“…A dimension of gender-role attitudes examined in only a few studies of body concerns and disturbed eating is one's stance with respect to feminist values and goals. Although some feminist attitudes about women's roles appear unrelated to measures of disturbed eating (Bailey & Hamilton, 1992) or relationships between body image and self-esteem (Mintz & Betz, 1986), relationships between body image and appearance concerns did differ for women divided into groups based on self-identification as feminists and suggested that feminists may use personal rather than external standards for body evaluations (Kelson, Kearney-Cooke, & Lansky, 1990).…”
mentioning
confidence: 98%